1992
DOI: 10.1016/s0022-5347(17)37588-2
|View full text |Cite
|
Sign up to set email alerts
|

The Detection of Prostate Specific Antigen, MHS-5, and Other Markers in Invasive Prostate Cancer and Seminal Vesicle

Abstract: Prostate specific antigen (PSA) is the most useful serum marker for following the disease status of prostate cancer patients after therapy. While PSA is felt to be an organ specific marker, lack of PSA expression in the seminal vesicles has not been adequately established. MHS-5 is a monoclonal antibody which recognizes an epitope on seminal vesicle specific antigen. Our objectives were to define PSA expression by the seminal vesicles, to determine whether MHS-5 could serve as an adjunct in the diagnosis of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Notably, one of the monoclonal antibodies used in both these studies [5,6] (‘ER‐PR8’) was also one component of the antibody mix used in the present study. In three older immunohistochemical studies of the seminal vesicle no PSA immunoreactivity was found [12–14]. We propose that these discrepancies are a result of differences in sample preparation, as all previous immunohistochemical studies [5,6,12–14] used either formalin‐ or Bouin‐fixed and paraffin‐embedded samples.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Notably, one of the monoclonal antibodies used in both these studies [5,6] (‘ER‐PR8’) was also one component of the antibody mix used in the present study. In three older immunohistochemical studies of the seminal vesicle no PSA immunoreactivity was found [12–14]. We propose that these discrepancies are a result of differences in sample preparation, as all previous immunohistochemical studies [5,6,12–14] used either formalin‐ or Bouin‐fixed and paraffin‐embedded samples.…”
Section: Discussionmentioning
confidence: 87%
“…In three older immunohistochemical studies of the seminal vesicle no PSA immunoreactivity was found [12–14]. We propose that these discrepancies are a result of differences in sample preparation, as all previous immunohistochemical studies [5,6,12–14] used either formalin‐ or Bouin‐fixed and paraffin‐embedded samples. Using formalin‐fixed and paraffin‐embedded tissue we also obtained very weak and inconsistent PSA signals, hardly above background staining.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation